SCRIBBLING WITH MALE EGO: ANALYSING THE MALE GAZE IN THE PORTRAYAL OF WOMEN IN CARTOONS - Thomas, Basil; Gem Cherian (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Male cartoonists dominated the cartoon industry of Keralam in the second half of the twentieth century. Women stereotypes are highlighted in the discourse of cartoons, probably like any other artform in the world. This paper is an attempt to analyse the representation of women folk in the cartoons of Keralam, during the post independent period of India. The cartoons of veteran male cartoonists namely Cartoonist Toms, Cartoonist Yesudasan and Cartoonist Thomas have been analysed for the study. The misrepresentation of women characters in their cartoons are analysed. The ‘domineering wife’ stereotype in the cartoons portraying the domestic setting and the household is not the fair representation of women of the time, given the patriarchal tradition. Women’s empowerment is shown mainly as their physical empowerment in the cartoon series. The male gaze in the commodification of female body in the cartoons is analysed. The male ego in the nurturing of ideal woman characters by the male cartoonists is problematized in the paper. The images used in this paper are collected from archives and the sources of images, as it is mentioned in the bibliography, are old collections of magazines, which are fifty years or more old. These cartoons are retrieved from the archives compiled at Appan Thampuran Smaraka Library in Thrissur, Kerala.